Ubiquitous energy conversion of two-dimensional molecular crystals. (12th February 2019) - Xu, Beibei; Hu, Yong; Guan, Ying-Shi; Zhang, Zhuolei; Ren, Shenqiang
Abstract: Two-dimensional (2D) atomic crystals have triggered significant excitement due to their rich physics as well as potential industrial applications. The possibility of a molecular counterpart with scalable processability and superior performance is intriguing from both fundamental and applied perspectives. Here, we present the freestanding 2D molecular charge-transfer bis(ethylenedithio)tetrathiafulvalene-C60 crystals prepared by a modified Langmuir–Blodgett method, with precisely controlled few-layer thickness and centimeter-scale lateral dimension. The interconversion of intrinsic excited process, the long-range ordering and anisotropic stacking arrangement of the molecular layered crystals generate external stimuli responsive behaviors and anisotropic spin-charge conversion with magnetic energy conversion ability, as well as a superior UV photosensitivity. Moreover, the 2D freestanding crystals demonstrate superior magneto-electrical properties. These results suggest that a new class of 2D atomically thin molecular crystals with novel electronic, optical and magnetic properties have great potential for spintronic, energy and sensor applications.